Die Sūtra's des Vedānta, oder die Cārīraka-Mīmāṅsā des Bādarāyaṇa nebst dem vollständigen commentare des Caṅkara - Śaṅkarācārya (F.A. Brockhaus, 1887)
Commentary on Bādarāyaṇa's Brahmasūtra, basic tenets of the Vedanta school in Hindu philosophy; includes translation in German.